2016
DOI: 10.1038/bjc.2016.142
|View full text |Cite
|
Sign up to set email alerts
|

Childhood leukaemia and distance from power lines in California: a population-based case-control study

Abstract: Background:Studies have reported an increased risk of childhood leukaemia associated with living near high-voltage electric power transmission lines that extend to distances at which magnetic fields from lines are negligible. We conducted a large records-based case-control study of childhood leukaemia risk in the population living near power lines in California.Methods:The study included 5788 childhood leukaemia and 3308 central nervous system (CNS) cancer cases (for comparison) born in and diagnosed in Califo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
2
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 20 publications
4
29
1
1
Order By: Relevance
“…The study design, including methods of case ascertainment and control selection [21], methods for calculated fields [22], and estimation of distance from birth residence to transmission lines and associated risks [14] have been previously described. We summarize them briefly here.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study design, including methods of case ascertainment and control selection [21], methods for calculated fields [22], and estimation of distance from birth residence to transmission lines and associated risks [14] have been previously described. We summarize them briefly here.…”
Section: Methodsmentioning
confidence: 99%
“…We previously reported on childhood leukemia risk in relation to the distance from birth address to nearby power transmission lines [14]. The current paper presents analysis of childhood leukemia risk in relation to the residential exposure to extremely low-frequency magnetic fields from nearby transmission lines and is the first study of calculated fields and childhood leukemia in the US.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another pooled analysis published the same year, which included 15 studies based on less restrictive inclusion criteria, showed a relative risk of 1.7 for exposure above 0.3 μT [29]. New studies are in line with these large pooled analyses [30,31,[174][175][176]. For example, a meta-analysis based on 11,699 cases and 13,194 controls showed that the relative risk was 1.57 for exposure above 0.4 μT [31].…”
Section: The Stem Cell Division Theory Of Cancer Provides a New Framementioning
confidence: 86%
“…Latter, a pooled analysis of seven studies published after 2000 reported a 1.4-fold increase in childhood leukemia among children with exposures of 0.3 μT or higher [6]. New studies are in line with these large pooled analyses, typically showing relative risks between 1.5 and 2 [7][8][9][10]. For example, in a meta-analysis based on 11,699 cases and 13,194 controls, the relative risk was 1.57 for exposure above 0.4 μT [10].…”
Section: Elf-emfs and Childhood Leukemia: Evidence Of Carcinogenicitymentioning
confidence: 90%